Primary transcatheter dilation of the pulmonary valve in cyanotic patients with tetralogy of Fallot and dominant pulmonary valve stenosis - Nathalie Mini; Claudia Arenz; Marian Mikus; Martin B. E. Schneider (Frontiers in Cardiovascular Medicine)
ObjectivesThis study reviews the outcome of pulmonary valve dilation (PVB) in patients with tetralogy of Fallot (TOF) and predominantly pulmonary valve stenosis as first palliation and the impact of balloon-related cusp tears (BRCTs) on the surgical strategy.BackgroundThe early management of cyanotic patients TOF is still controversial.MethodsThis was a retrospective study of 19 patients with TOF who underwent PVB over 4 years. Differential growth of the pulmonary valve/annulus (PV) and arteries was documented, as was differential saturation improvement. Surgical findings were analyzed, including BRCT and subsequent surgical methods.ResultsThe median saturation value improved significantly from 70% (45%–98%) to 90% (74%–98%) (p-value = 0.03). Recurrent desaturation 7–45 days after the intervention occurred in 7 patients; 2 needed reinterventions, and 5 needed an early repair. At the time of repair, the median PV z-score improved from −3.7 (−6.12 to −1.3) to −2.1 (−4.2 to −0.19) (p-value = 0.2). The LPA z-score improved from −1.95 (−3.4 to −0.4) to 0.36 (−2.9 to 1.8) (p-value = 0.2), and the RPA z-score improved from −2 (−2.8 to 0.04) to 0.18 (−2.4 to 1.3) (p-value = 0.34). The mean pressure gradient decreased from 50 mmHg (32–72) to 38 mmHg (20–55) (p-value 0.08). The surgical repair was on time in 13 patients; one was still waiting for surgery. BRCTs were found in 8 patients and had no impact on the surgical strategy. Seven patients needed transannular patching, and in 11, the PV could be preserved (including 7 with BRCTs).ConclusionPalliative transcatheter dilation of predominantly pulmonary valve stenosis in patients with TOF and predominantly pulmonary valve stenosis is safe and effective in palliating cyanosis in most patients. It can improve saturation and prompt pulmonary development, delaying the surgical repair to the right time. A subsequent BRCT seems to have no negative impact on the surgical strategy.